Foliar application of iron-lysine to boost growth attributes, photosynthetic pigments and biochemical defense system in canola (Brassica napus L.) under cadmium stress - Mohammad K. Okla; Muhammad Hamzah Saleem; Ibrahim A. Saleh; Naser Zomot; Shagufta Perveen; Abida Parveen; Fozia Abasi; Habib Ali; Baber Ali; Yasmeen A. Alwasel; Mostafa A. Abdel-Maksoud; Mükerrem Atalay Oral; et al. (BMC Plant Biology, 2023)
Abstract In the current industrial scenario, cadmium (Cd) as a metal is of great importance but poses a major threat to the ecosystem. However, the role of micronutrient − amino chelates such as iron − lysine (Fe − lys) in reducing Cr toxicity in crop plants was recently introduced. In the current experiment, the exogenous applications of Fe − lys i.e., 0 and10 mg L − 1, were examined, using an in vivo approach that involved plant growth and biomass, photosynthetic pigments, oxidative stress indicators and antioxidant response, sugar and osmolytes under the soil contaminated with varying levels of Cd i.e., 0, 50 and 100 µM using two different varieties of canola i.e., Sarbaz and Pea − 09. Results revealed that the increasing levels of Cd in the soil decreased plant growth and growth-related attributes and photosynthetic apparatus and also the soluble protein and soluble sugar. In contrast, the addition of different levels of Cd in the soil significantly increased the contents of malondialdehyde (MDA) and hydrogen peroxide (H2O2), which induced oxidative damage in both varieties of canola i.e., Sarbaz and Pea − 09. However, canola plants increased the activities of superoxide dismutase (SOD), peroxidase (POD), catalase (CAT), and non-enzymatic compounds such as phenolic, flavonoid, proline, and anthocyanin, which scavenge the over-production of reactive oxygen species (ROS). Cd toxicity can be overcome by the supplementation of Fe − lys, which significantly increased plant growth and biomass, improved photosynthetic machinery and sugar contents, and increased the activities of different antioxidative enzymes, even in the plants grown under different levels of Cd in the soil. Research findings, therefore, suggested that the Fe − lys application can ameliorate Cd toxicity in canola and result in improved plant growth and composition under metal stress.